Performing sovereignty: war documentaries and documentary wars in Syria - Galván-Álvarez, Enrique (European Journal of English Studies, 2018)
This essay explores the images emerging from the Syrian conflict through the genre of war documentaries by focusing on the performance of sovereignty. Drawing on Foucault's notion of governmentality and Butler's performative theory, the author looks at states as performative agents that stage power in front of the camera as a form of self-legitimisation. War documentaries are part of a documentary war in which image, information and emotional involvement have become weaponised. He assesses a few examples of religious and secular sovereignty performed for journalists who are embedded with various militias. This genre is brought about through cooperation between the embedded reporters (i.e. working inside an army or militia) and the fighters assigned to protect and show them around the territory they control. This results in a symbiotic relationship in which both sides co-produce a heavily mediated image of the war from the inside, one that satisfies the journalist's desire for exclusive access' and the fighter's desire for recognition. Such a representational pact contributes a unique feature to the war documentary genre in which the films show the raw reality of war as much they offer an opportunity to perform the state before the camera. From this perspective, the fighters appear not only as destroyers but as builders of a new order, thus complicating the image of the jihadi as an irrational, nihilistic and violent subject.
Keywords: governmentality; Syrian Civil War; war documentaries; sovereignty; performance; Vice News; gonzo journalism; JCR; Scopus